The rebirth of general relativity: theses and historiographical perspectives - Ferreira, Juliana Correia; Youssef, Juliana; Hartz, Thiago (Cadernos de Astronomia, 2025)
In this article, we discuss the thesis, common among physicists and historians, that, after three decades of stagnation, there was a “renaissance” of interest in general relativity in the 1950s and 1960s. We present two versions of this thesis: one places the shift in the 1950s, following the first conferences dedicated to general relativity, and the other identifies the shift in the 1960s, due to advancements in astrophysics. We review the main arguments supporting this thesis by physicists and historians, recall some of the criticisms it has received, and analyze the key historical evidence that emerges in this historiographical debate. Finally, we reflect on the validity of this thesis and on the current challenges in research on the history of general relativity.
Keywords: History of Physics; General Relativity; Albert Einstein; Historiography